Applying Creativity Research to Cooking. (28th November 2015) - Beghetto, Ronald A.; Kaufman, James C.; Hatcher, Ryan
Abstract: What, if any, benefit might there be to applying creativity research to cooking? The purpose of this paper was to address this question. Specifically, we draw on concepts and theories from creativity research to help clarify what is meant by creative cooking. This includes exploring creative cooking through the lens of the 4‐C and Propulsion models of creativity. We close with a brief discussion of why applying creativity research to cooking is both beneficial and an area in need of further work.